2020
DOI: 10.1002/jeab.577
|View full text |Cite
|
Sign up to set email alerts
|

Investigations of operant ABA renewal during differential reinforcement

Abstract: Operant renewal is a form of relapse in which a previously extinguished response recurs due to a change in context. We designed two experiments to examine the impact of differential reinforcement of alternative behavior on ABA renewal in a translational model of relapse with 12 children. We compared levels of renewal in two 3-phase arrangements. In one arrangement, we reinforced target responding in Context A, extinguished responding in Context B, and returned to Context A while continuing to implement extinct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 45 publications
(80 reference statements)
1
20
0
Order By: Relevance
“…Authors tended to vary in their categorization of delayed effects as renewal (e.g., Liddon et al, ; Podlesnik et al, ). Additionally, some authors (e.g., Kimball et al, ; Saini et al, ) did not describe modest increases in target behavior as renewal despite our definition detecting an increase in target responding from the last session of Phase 2 compared to the first session of Phase 3.…”
Section: Resultsmentioning
confidence: 73%
See 3 more Smart Citations
“…Authors tended to vary in their categorization of delayed effects as renewal (e.g., Liddon et al, ; Podlesnik et al, ). Additionally, some authors (e.g., Kimball et al, ; Saini et al, ) did not describe modest increases in target behavior as renewal despite our definition detecting an increase in target responding from the last session of Phase 2 compared to the first session of Phase 3.…”
Section: Resultsmentioning
confidence: 73%
“…Podlesnik et al () reported that adults ages 19‐21 years old participated. Kimball et al () indicated that children were 2‐18 ( M = 4.25) years old. M = male.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent translational research on DRA-based interventions has shown that destructive behavior is likely to reemerge under certain conditions, such as when the alternative response fails to produce the functional reinforcer (Berg et al, 2015;Fisher et al, 2020;Fisher, Greer, Fuhrman et al, 2018;Fisher, Saini et al, 2018;Fuhrman et al, 2016;Greer et al, 2020;Hoffman & Falcomata, 2014;Lieving et al, 2004;Mace et al, 2010;Marsteller & St. Peter, 2014;Volkert et al, 2009;Wacker et al, 2011;Wacker et al, 2013) and following other decrements in the rate of alternative reinforcement (Briggs et al, 2018;Volkert et al, 2009). This reemergence of destructive behavior following successful treatment is known as treatment relapse (Pritchard et al, 2014), and researchers are increasingly concerned with how different forms of relapse (e.g., resurgence, renewal, reinstatement) affect clinical care (e.g., Briggs et al, 2018;Craig, Sullivan, Browning et al, 2019;Kimball et al, 2020;Kimball et al, 2018;Podlesnik & DeLeon, 2015). Translational researchers have placed considerable focus on resurgence, or the reemergence of previous behavior resulting from a general worsening of reinforcement conditions (Epstein, 1985;Lattal et al, 2017), as such conditions occur frequently in and outside the clinic.…”
mentioning
confidence: 99%